Polyamines in renal failure - Igarashi, K; Ueda, S; Yoshida, K; Kashiwagi, K (Amino acids, 2006)
The levels of polyamines (putrescine, spermidine and spermine) and polyamine oxidase in plasma of patients with chronic renal failure were determined. The level of putrescine was increased but the level of spermine was decreased in the plasma of these patients. The patients also had increased plasma polyamine oxidase activity leading to increased degradation of spermine. As acrolein was a major toxic compound produced from spermine by polyamine oxidase, the levels of free and protein-conjugated acrolein in plasma were also measured. Acrolein levels were enhanced in plasma of patients with chronic renal failure. The accumulated acrolein found as protein conjugates was equivalent to 170 μM, which was about 5-fold higher than in plasma of normal subjects. It was found that acrolein is mainly produced by spermine oxidase in plasma. An increase in putrescine, spermine oxidase and acrolein in plasma was observed in all cases such as diabetic nephropathy, chronic glomerulonephritis and nephrosclerosis. After patients with chronic renal failure had undergone hemodialysis, their levels of plasma polyamines, spermine oxidase and acrolein returned towards normal. It is likely that acrolein produced from spermine accumulates in the blood due to decreased excretion into urine and may function as a uremic “toxin”.